2021
DOI: 10.1186/s12711-021-00654-x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies to optimize genomic selection in honey bees

Abstract: Background With the completion of a single nucleotide polymorphism (SNP) chip for honey bees, the technical basis of genomic selection is laid. However, for its application in practice, methods to estimate genomic breeding values need to be adapted to the specificities of the genetics and breeding infrastructure of this species. Drone-producing queens (DPQ) are used for mating control, and usually, they head non-phenotyped colonies that will be placed on mating stations. Breeding queens (BQ) he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…A previous attempt to propose an easier method to evaluate recapping ended with unconvincing results, such as low heritabilities and low correlations with mite infestation ( Guichard et al 2021 ). The development of genome-based methods, however, appears promising to gain knowledge on the genetic background of recapping and to enable the emergence of genomic marker-assisted selection ( Brascamp et al 2018 , Bernstein et al 2021 , Guichard et al 2022 ), which might help increase the speed of genetic progress. Our results confirm the difficulty of identifying suitable traits for successful resistance selection programs but suggest that recapping is one of the promising candidate traits that may lead to colonies with an elevated resistance against Varroa destructor , or at least a significant reduction in the need for miticide treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A previous attempt to propose an easier method to evaluate recapping ended with unconvincing results, such as low heritabilities and low correlations with mite infestation ( Guichard et al 2021 ). The development of genome-based methods, however, appears promising to gain knowledge on the genetic background of recapping and to enable the emergence of genomic marker-assisted selection ( Brascamp et al 2018 , Bernstein et al 2021 , Guichard et al 2022 ), which might help increase the speed of genetic progress. Our results confirm the difficulty of identifying suitable traits for successful resistance selection programs but suggest that recapping is one of the promising candidate traits that may lead to colonies with an elevated resistance against Varroa destructor , or at least a significant reduction in the need for miticide treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic variance for honeybee colonies equals [ Brascamp and Bijma 2019 ; Bernstein et al 2021 , Equation (2)]. …”
Section: Theorymentioning
confidence: 99%
“…Instead, both phenomena were consequences of incomplete phenotype records due to preselection strategies. Thus, in comparison with other factors that influence breeding success in honeybees, such as mating control (Du et al, 2021a; Plate et al, 2019b) or the inclusion of genomic data in the relationship matrix (Bernstein et al, 2021; Brascamp et al, 2018; Gupta et al, 2013), the use of correct genetic parameters in single‐trait selection appears secondary. The results clearly suggest that BLUP selection is a viable option in honeybee breeding, also for incipient breeding programmes where genetic parameters cannot yet be estimated with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, earlier studies have shown that this ratio can be heavily influenced by the mating strategy of the breeding programme (Du et al, 2021a; Kistler et al, 2021; Plate et al, 2019b). Furthermore, Bernstein et al (2021) showed that the inclusion of genomic queen data into the BLUP evaluations shifts the breeding focus towards the maternal effects.…”
Section: Discussionmentioning
confidence: 99%